Direct Investment and Local Content Rules in the European Community - Thomas Andersson (The Research Institute of Industrial Economics (IUI), 1990)
This paper analyses the behaviour of competing governments in the EC with respect to inflows of direct investment. Solving a non-cooperative sequential bargaining game in which host countries gain from direct investment through tax revenue or imposition of forced local subcontracting, it is concluded that a successful 1992 program does not allow discrimination of direct investment. As they bid against each other for the attraction of projects, the EC countries will give away rents generated by protectionism. Hence, multinational firms may temper the emergence of trading 'blocs' through their ability to play individual countries against each other.
Keywords: C72; C78; F21; 330; Direct investment; Game theory; Multinational firms